Children's well-being at schools: Impact of climatic conditions and air pollution. (September 2016) - Salthammer, Tunga; Uhde, Erik; Schripp, Tobias; Schieweck, Alexandra; Morawska, Lidia; Mazaheri, Mandana; Clifford, Sam; He, Congrong; Buonanno, Giorgio; Querol, Xavier; Viana, Mar; Kumar, Prashant
Abstract: Human civilization is currently facing two particular challenges: population growth with a strong trend towards urbanization and climate change. The latter is now no longer seriously questioned. The primary concern is to limit anthropogenic climate change and to adapt our societies to its effects. Schools are a key part of the structure of our societies. If future generations are to take control of the manifold global problems, we have to offer our children the best possible infrastructure for their education: not only in terms of the didactic concepts, but also with regard to the climatic conditions in the school environment. Between the ages of 6 and 19, children spend up to 8 h a day in classrooms. The conditions are, however, often inacceptable and regardless of the geographic situation, all the current studies report similar problems: classrooms being too small for the high number of school children, poor ventilation concepts, considerable outdoor air pollution and strong sources of indoor air pollution. There have been discussions about a beneficial and healthy air quality in classrooms for many years now and in recent years extensive studies have been carried out worldwide. The problems have been clearly outlined on a scientific level and there are prudent and feasible concepts to improve the situation. The growing number of publications also highlights the importance of this subject. High carbon dioxide concentrations in classrooms, which indicate poor ventilation conditions, and the increasing particle matter in urban outdoor air have, in particular, been identified as primary causes of poor indoor air quality in schools. Despite this, the conditions in most schools continue to be in need of improvement. There are many reasons for this. In some cases, the local administrative bodies do not have the budgets required to address such concerns, in other cases regulations and laws stand in contradiction to the demands for better indoor air quality, and sometimes the problems are simply ignored. This review summarizes the current results and knowledge gained from the scientific literature on air quality in classrooms. Possible scenarios for the future are discussed and guideline values proposed which can serve to help authorities, government organizations and commissions improve the situation on a global level. Graphical abstract: Highlights: Recent literature on the air quality in school environments is reviewed. Urbanization and climate change adversely affect the air quality in classrooms. Carbon dioxide is not the sole key parameter for ventilation control. Sources of gaseous pollutants and particulate matter in classrooms are discussed. Advanced IAQ guidelines are required to improve the performance in schoolwork.